The Role of Transformational Leadership and Effective Communication on the Implementation of Patient Safety With Trust as Mediation at X Hospital Jakarta - Vivi Silvia; Rokiah Kusumapradja; Idrus Jus'at (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2021)
Patient safety has become a global issue in the field of health service including hospital. Implementation of patient safety in the hospital requires the involvement of leadership, effective communication and patient’s trust. At X Hospital Jakarta, the root case that frequently occurs on patient safety incident is communication matter. This has an impact on the reoccurrence of patient safety incident. This research aims to analyze the influence of transformational leadership and effective communication towards the implementation of patient safety by trust as mediation. The method of this research is causal associative with quantitative approach. There are 37 nurses as samples counted with G-Power Statistics application. The technique of collecting data uses primary data questionnaires and is processed by path analysis. The result shows that there is a great influence on transformational leadership towards trust. Therefore, in implementing patient safety in hospital, it needs program development on transformational leadership; controlling, and evaluating the implementation of effective communication; and improving nursing care as a form of professional nursing practice to create and to maintain patient’s trust towards nurse.